2009
DOI: 10.1007/s11430-009-0154-4
|View full text |Cite
|
Sign up to set email alerts
|

Zircon U-Pb geochronological framework of Qitianling granite batholith, middle part of Nanling Range, South China

Abstract: The Qitianling granite batholith (QGB) is located in the southern Hunan Province, middle part of the Nanling Range, South China. Its total exposure area is about 520 km 2 . Based on our 25 single grain zircon U-Pb age data and 7 published data as well as the geological, petrological, and space distribution characteristics, we conclude that QGB is an Early Yanshanian (Jurassic) multi-staged composite pluton. Its formation process can be subdivided into three major stages. The first stage, emplaced at 163-160 Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 18 publications
4
28
0
Order By: Relevance
“…The origin of the Changchengling (~178 Ma) and Ningyuan (~174 Ma) basaltic rocks in southern Hunan (Jiang et al 2009) and the Dexing adakitic porphyries (~171 Ma) in northeastern Jiangxi (Zhou et al 2012) (Fig. 1a) Zhu et al 2006a, b;Qitianling (QTL), Zhu et al 2009;Jinjiling (JJL) and Xishan (XS), Jiang et al 2009; Huashan (HS), Zhu et al 2006a; Guposhan (GPS), Zhu et al 2006b]; b Simplified geological map of the Tangquan pluton; c Simplified geological map of the Xiadao pluton A-type granites in the Shi-Hang zone (Fig. 1a) (e.g., Jiang et al 2006a;2009).…”
Section: Geological Setting and Geology Of The Granitoidsmentioning
confidence: 99%
“…The origin of the Changchengling (~178 Ma) and Ningyuan (~174 Ma) basaltic rocks in southern Hunan (Jiang et al 2009) and the Dexing adakitic porphyries (~171 Ma) in northeastern Jiangxi (Zhou et al 2012) (Fig. 1a) Zhu et al 2006a, b;Qitianling (QTL), Zhu et al 2009;Jinjiling (JJL) and Xishan (XS), Jiang et al 2009; Huashan (HS), Zhu et al 2006a; Guposhan (GPS), Zhu et al 2006b]; b Simplified geological map of the Tangquan pluton; c Simplified geological map of the Xiadao pluton A-type granites in the Shi-Hang zone (Fig. 1a) (e.g., Jiang et al 2006a;2009).…”
Section: Geological Setting and Geology Of The Granitoidsmentioning
confidence: 99%
“…The outcropping strata in the belt consists of Sinian to Cambrian low-grade metamorphic rocks, Devonian to Lower Triassic limestone intercalated with clastic rocks, and Upper Triassic to Tertiary sandstone and siltstone. The Yangshanian granites intrude extensively in southern Hunan with the largest being the Qitianling intrusion [31][32][33], and they control the formation of a number of large-scale porphyry, skarn, and vein-type W-Sn-Pb-Zn deposits (Figure 1b), e.g., the Shizhuyuan [34], Baoshan [35], Huangshaping [36][37][38], Xianghualing [39], Xintianling [35], Yaoganxiang [30], Baiyunxian, and Furong deposits [35,40].…”
Section: Geologic Settingmentioning
confidence: 99%
“…While these tectonic events were responsible for multi-stage granitic intrusive bodies, the crust-mantle interaction played an important role in the formation of the granitic rocks (Chen, 1989;Zhu et al, 2009). Mao et al (2009) have suggested a comprehensive deposit model related to magma intrusions in South China (Fig.2).…”
Section: Geological Settingsmentioning
confidence: 99%